SECURE E-PAYMENT METHOD BASED ON VISUAL CRYPTOGRAPHY - Yuniati - NIM: 23515009 , Trihastuti
In recent time there is a rapid growth in online shopping market. With ever increasing popularity of online shopping, debit or credit card fraud and personal information security are major concerns for all participants, especially for customers. Phishing and identity theft are common threats of online shopping. Phishing is a method of stealing personal confidential informations, such as username, passwords, credit card details, from legitimate user. In this study, we have proposed a credit card payment method using visual cryptography. The purpose is to improve e-payment security, especially in terms of authentication, authorization, and confidentiality. In the proposed method, visual cryptography is applied in three functions: 1) authentication between user and merchant, 2) authentication between user and card provider, 3) user authorization towards card issuer. At the 1st function, visual cryptography is applied to captcha image generated by merchant server during user registration phase. It uses scheme (2, 2) with 2-subpixel expansion. At the 2nd function, visual cryptography is applied to a textfile containing credit card information sent by merchant to the card provider. It uses scheme (2, 2) with pixel replacement. At the 3rd function, visual cryptography is applied to QR Code containing OTP that is used to authorize the payment transaction. It uses scheme (2, 2) with 4-subpixel expansion. A prototype will be built and several test cases will be carried out to simulate and analyze the security of the proposed method. The test results show that the proposed method is able to prevent phishing and identity theft, in sense that authentication, authorization, and confidentiality are gained. Phishing can be prevented because only legitimate participant who has an image share resulted from visual cryptography. Identity theft can be prevented because credit card details are not stored in the merchantÃ‚Â’s database. Authorization is more guaranted because only authenticated user can makes transactions and authorizes the payments.